High detection sensitivity achieved with cryogenic detectors in combination with matrix-assisted laser desorption / ionisation time-of-flight mass spectrometry (MALDI-TOF MS); European Journal of Mass Spectrometry; Vol. 10, iss. 4 - Christ P.; Rutzinger S.; Koy C.; Seidel W.; Uchaykin S. V. Sergey Victorovich; Glocker M. O.; Probst F. (2004, 2004)
Title screen